Methodological proposal for studying suicide as a complex phenomenon - Minayo Maria Cecília de Souza; Cavalcante Fátima Gonçalves; Souza Edinilsa Ramos de (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2006)
The authors present a methodological proposal for studying suicide and suicide attempts from a combined socio-anthropological, epidemiological, and psychosocial perspective. This interdisciplinary and complex research model simultaneously examined individual, socioeconomic, historical/cultural, and population data as few studies have succeeded to date. Considering that the present study was conducted in a specific social reality, the authors created a methodological approach to comprehend the effects of a crisis in an industrial restructuring process in a mining company town in the State of Minas Gerais, Brazil, that was associated with unusually high suicide rates. Since it referred to a small geographic area (with only 100,000 inhabitants), the research is considered an ideal case study. The authors created different strategies to trace the local epidemiological profile, adapted a psychosocial autopsy technique to elucidate suicide cases and a psychosocial harm assessment technique to comprehend suicide attempts, and conducted a local analysis of the socio-cultural context. The methods proposed here (with advantages and limitations) proved productive for elucidating the study hypothesis.